Efficacy and Outcomes of Intrathecal Analgesia as Part of an Enhanced Recovery Pathway in Colon and Rectal Surgical Patients. (1st March 2018) - Merchea, Amit; Lovely, Jenna K.; Jacob, Adam K.; Colibaseanu, Dorin T.; Kelley, Scott R.; Mathis, Kellie L.; Spears, Grant M.; Huebner, Marianne; Larson, David W.
Abstract : Purpose . Multimodal analgesia is an essential component of an enhanced recovery pathway (ERP). An ERP that includes the use of single-injection intrathecal analgesia (IA) has been shown to decrease morbidity and cost and shorten length of stay (LOS). Limited data exist on safety, feasibility, and the optimal IA regimen. Our objective was to characterize the efficacy, safety, and feasibility of IA within an ERP in a cohort of colorectal surgical patients. Methods . We performed a retrospective review of all consecutive patients aged ≥ 18 years who underwent open or minimally invasive colorectal surgery from October 2012 to December 2013. All patients were enrolled in an institutional ERP that included the use of single-injection IA. Demographics, anesthetic management, efficacy (pain scores and opiate consumption), postoperative ileus (POI), adverse effects, and LOS are reported. Results . 601 patients were identified. The majority received opioid-only IA (91%) rather than a multimodal regimen. Median LOS was 3 days. Overall rate of ileus was 16%. Median pain scores at 4, 8, 16, 24, and 48 hours were 3, 2, 3, 4, and 3, respectively. There was no difference in postoperative pain scores, LOS, or POI based on intrathecal medication or dose received. Overall, development of respiratory depression (0.2%) or pruritus (1.2%) was rare. One patient required blood patch for postdural headache. Conclusion . Intrathecal analgesia is safe, feasible, and efficacious in the setting of ERP for colorectal surgery. All regimens and doses achieved a short LOS, low pain scores, and a low incidence of POI. This trial is registered with Clinicaltrails.govNCT03411109 .